Il nuovo ordine pubblico concordatario (Stato, Chiese e pluralismo confessionale, 2015)
Contributo sottoposto a valutazioneSOMMARIO: 1. Premessa - 2. Ordine pubblico e delibazione delle sentenze ecclesiastiche di nullità matrimoniale – 3. La sentenza n. 16379 del 2014: a) il concetto di convivenza coniugale triennale; b) le contraddizioni della Corte – 4. Un’impostazione giuridicamente logica e metodologicamente corretta - 5. Le “sottintese” esigenze di tutela: a) del coniuge c.d. economicamente debole; b) del coniuge ateo - 6. Conclusioni. Abstract: In the decision n. 16379/2014, the Italian Supreme Court states that three years of conjugal life is an obstacle to the exequatur procedure of the ecclesiastical sentences of nullity of marriage. This statement has already been supported by other decisions taken by the Court during 2015 and has de facto determined a new public policy, valid only for ecclesiastical sentences but not, for example, applicable to judgments made abroad. This new public policy is more restrictive than both the international public policy and the Italian public policy.